PERHITUNGAN UNIT COST TINDAKAN BEDAH APPENDIKTOMI DI KAMAR OPERASI RSD MADANI PROVINSI SULAWESI TENGAH - Yulianisel, Yulianisel (Katalogis, 2015)
This study aims to determine the unit cost of action appendectomy in hospital operating rooms Madani area of ​​Central Sulawesi Province by calculating the cost of direct and indirect damages. This research is a descriptive operational research and analysis using secondary data Hospitals in 2014 at the Regional Hospital Madani Central Sulawesi province. Method of calculating the cost of using the ABC method (Activity Based Costing) and simple distribution. ABC method for allocating direct costs by calculating the cost of activities that occur using cost driver based time activities. Simple distribution method for allocating indirect costs distribution costs from support units to units of production (operating room). The results showed appendectomy actual unit cost of Rp. 2,376,419, and the normative unit cost of Rp. 2,347,847, -. The operational costs of medical and paramedic services constitute the largest expense